Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Hattori Heiji
Xem chi tiết
Nguyễn Thị Quỳnh
Xem chi tiết
Bùi Thị Vân
9 tháng 11 2017 lúc 9:40

\(A=\left(\frac{x^2-1}{x^4-x^2+1}-\frac{1}{x^2+1}\right).\left(x^4+\frac{1-x^4}{1+x^2}\right)\)
\(=\left(\frac{\left(x^2-1\right)\left(x^2+1\right)-\left(x^4-x^2+1\right)}{\left(x^4-x^2+1\right)\left(x^2+1\right)}\right).\left(x^4+\frac{\left(1+x^2\right)\left(1-x^2\right)}{1+x^2}\right)\)
\(=\frac{x^4-1-x^4+x^2-1}{\left(x^2+1\right)\left(x^4-x^2+1\right)}\left(x^4+1-x^2\right)\)
\(=\frac{x^2-2}{x^2+1}\).

êfe
Xem chi tiết
Clary Đăng
Xem chi tiết
Clary Đăng
Xem chi tiết
VN in my heart
27 tháng 6 2016 lúc 21:03

\(=3x^3-\frac{3}{2}x^2-x^3-\frac{1}{2}x+\frac{1}{2}x+2\)

\(=2x^3-\frac{3}{2}x^2+2\)

Linh Dao
Xem chi tiết
Nguyễn Lê Phước Thịnh
30 tháng 1 2022 lúc 0:26

\(A=\left(\dfrac{1}{x-2}+\dfrac{2x}{\left(x-2\right)\left(x+2\right)}+\dfrac{1}{x+2}\right)\cdot\dfrac{2-x}{x}\)

\(=\dfrac{x+2+2x+x-2}{-\left(2-x\right)\left(x+2\right)}\cdot\dfrac{2-x}{x}\)

\(=\dfrac{4x}{-\left(x+2\right)\cdot x}=\dfrac{-4}{x+2}\)

Trương Bảo Hân
Xem chi tiết
Thiên Mob
Xem chi tiết
Nuyen Thanh Dang
Xem chi tiết